High Fluorescence Lymphocyte Count Percentage and its Utility in the Diagnosis of Dengue - S. Nandhini; Sri Gayathri; M Arthi; Banukeerthana Rajasekaran (Journal of Applied Hematology, 2025)
CONTEXT: Dengue fever is a mosquito-borne tropical disease caused by the dengue virus, presenting a wide range from asymptomatic to severe symptoms like high fever and hemorrhagic fever. Early diagnosis and differentiation from other acute febrile illnesses (AFIs) are critical. This study assesses the high fluorescence lymphocyte count percentage (HFLC%) from hematology analyzers as a preliminary diagnostic tool for dengue. AIMS: To analyze the HFLC% between dengue-positive and dengue-negative acute febrile states and derive the cutoff value for HFLC% for predicting dengue fever. SETTINGS AND DESIGN: A prospective laboratory study. SUBJECTS AND METHODS: A total of 160 dengue serology-positive cases and 160 cases of AFI who were dengue-negative (serving as controls) were chosen. Dengue-positive cases were diagnosed based on immunoglobulin M antibody titers, and a cutoff of more than 11 IU/dL was taken as positive. HFLC% from the Sysmex XN-3100 analyzer was obtained, tabulated, and analyzed. STATISTICAL ANALYSIS USED: IBM SPSS Statistics software 23 was used for descriptive statistics and plotting receiver operating characteristic curve. RESULTS: Among 160 dengue-positive cases, there were 89 males and 71 females, with a mean age of 24. In nondengue cases, there were 74 males and 86 females with a mean age of 43 years. The dengue-positive group showed significantly higher HFLC% (5.62%) compared to dengue-negative controls (0.42%). The receiver operator curve indicated an HFLC cutoff at 3.39% with a specificity of 88.7% and sensitivity of 77.5%. Statistical significance was confirmed with P < 0.001. CONCLUSIONS: HFLC% shows good promise as a screening tool for early diagnosis of dengue in resource-limited setups and estimates the severity of dengue fever at an early stage which can help reduce the economic burden. HFLC% of more than 3.39% is suggestive of dengue fever, and higher values may indicate aggressive clinical progression. As complete blood counts are routinely ordered, these findings are beneficial, especially in situations with limited resources in endemic areas, where the initial HFLC%, being cheaper, could help initially screen patients for dengue fever and encourage further investigations which include more specific testing modalities such as NS1 antigen levels and initiate medication earlier with better outcome.